2014
DOI: 10.1080/16522354.2014.11073580
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Capabilities and Superior Firm Performance in the Uk Media Industry

Abstract: The past decade has seen a transformation in the way television broadcasters have managed their businesses. This paper examines the theory of 'dynamic capability' in two UK television broadcasters, BskyB and ITV, and their attempts to transform themselves into multi-product, multi-platform media companies. Using Comparative Financial Analysis and Content Analysis in a time series, this paper illustrates how the strategic management of media firms can be significantly different for two companies operating in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 20 publications
(46 reference statements)
0
26
0
Order By: Relevance
“…This criticism, is to an extent justified, particularly as Dixon et al (2014, 186) referred to dynamic capabilities as a "black box" with unknown contents. However, the recent work by Oliver (2014) presented a conceptual framework which focussed on specific variables that could be attributed to dynamic capabilities traits and applied these to UK media firms in a longitudinal analysis of dynamic capabilities and superior firm performance. This work argued that organisations' can renew, refresh and leverage new capabilities and competencies in order to successfully adapt to turbulent markets conditions by setting corporate objectives and implementing a strategy that: -is aspirational and stretches the organisation in to winning position in the market place;…”
Section: Literature Reviewmentioning
confidence: 99%
“…This criticism, is to an extent justified, particularly as Dixon et al (2014, 186) referred to dynamic capabilities as a "black box" with unknown contents. However, the recent work by Oliver (2014) presented a conceptual framework which focussed on specific variables that could be attributed to dynamic capabilities traits and applied these to UK media firms in a longitudinal analysis of dynamic capabilities and superior firm performance. This work argued that organisations' can renew, refresh and leverage new capabilities and competencies in order to successfully adapt to turbulent markets conditions by setting corporate objectives and implementing a strategy that: -is aspirational and stretches the organisation in to winning position in the market place;…”
Section: Literature Reviewmentioning
confidence: 99%
“…As such, the premise of this paper argues that it is the ability of a media firm to adapt their firm that can provide them with an 'adaptive advantage' in the market place, and that this type of advantage can be considered to be an aspect of superior firm performance. This is demonstrated by: firstly, dynamic capabilities being considered as the link between firm resources and the competitive media environment (Lampel and Shamsie, 2003;Owers and Alexander, 2011;Lawton and Rajwani, 2011;Doyle, 2013;Oliver 2016); secondly, that dynamic capabilities refer to the drive and enthusiasm of a media firm to renew resources in order to generate value and economic rents (Eisenhardt and Martin, 2000; and thirdly, dynamic capabilities refer to the management of firm resources that creates and sustains competitive advantages that cannot easily be imitated by competitors, and as such, this provides the basis for superior inter-firm performance (Teece and Pisano, 1994;Zollo and Winter, 2002;Post et al (2005;Oliver, 2014).…”
Section: Positioning This Researchmentioning
confidence: 99%
“…In the media context, Miller and Shamise (1996) concluded that resource reconfiguration in major U.S. film studios resulted in superior performance outcomes in the form of return on sales, market share, and firm profits. A more recent study by Oliver (2014) concluded that superior firm performance outcomes could be assessed using corporate financial analysis using the resource based ratios of Return on Capital Employed, Net Profit Margin and Asset Turnover. In addition, Naldi, Wikström and von Rimscha (2014, p.77) found dynamic capabilities performance effects in terms of taking creative ideas and developing them into a "new value proposition" (innovation) for small and medium-size audiovisual firms in Europe.…”
Section: Dynamic Capabilities and Superior Media Firm Performancementioning
confidence: 99%
“…Findings presented here build upon earlier work which is concerned with empirically investigating the connection between patterns of investment and resource usage within media firms and their ability to adjust, perform successfully and derive new revenues in the digital environment (Oliver, 2014;Picard, 2011). However, this article seeks to extend earlier work about the migration of media suppliers towards a multi-platform approach in two important ways.…”
Section: Introductionmentioning
confidence: 99%